Diseño de productos turísticos alternativos comunitarios para diversificar la oferta turística en la parroquia Balsapamba, cantón San Miguel provincia Bolívar, año 2018 - Puente Camacho, Diana Margarita (2020)
The present work was carried out in the Balsapamba parish belonging to the San Miguel de Bolívar canton, which is a design of alternative community tourism products that link the sectors that present tourism potential in this way it was observed that the communities that work in the tourism sector and the same are found with better accessibility to its attractions such as Copalillo, El Limon, Angas, La Plancha, Santa Lucia, in addition this research project has as a fundamental objective to potentiate the tourist resources of this sector of the Bolivar province to thus to be able to diversify the tourist offer of Balsapamba; To fulfill our project, we worked with a methodology based on Sampieri, it was descriptive, documentary-bibliographic and field, the techniques used to comply with three objectives were: the survey, the interview and also, we use inventory records Tourism of the Ministry of Tourism. In the study area, 5 communities were chosen that will have a great tourist potential where the inventory of tourist attractions was raised, identifying 11 attractions, 4 of which are cultural manifestations and 7 are natural attractions with which we have worked on the product proposal Alternative tourist With the data analysis, important results were obtained for our research in such a way that we have concluded in the creation of a global product called “Balsapamba adventure, nature and culture” as a whole, but within it are our 5 alternative community products that will contribute to the offer of the Balsapamba parish.